2007
DOI: 10.4141/cjas06032
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing corn or corn-barley diets with an E. coli derived phytase decreases total and soluble P output by weanling and growing pigs

Abstract: . 2007. Supplementing corn or corn-barley diets with an E. coli derived phytase decreases total and soluble P output by weanling and growing pigs. Can. J. Anim. Sci. 87: 353-364. The efficacy of an E. coli derived phytase on phosphorus (P) digestibility and excretion, on the form of the P excreted, and the optimal dietary calcium (Ca):P ratio was examined. In exp. 1, 63 barrows (40.4 ± 1.9 kg) were assigned to receive one of 21 treatments arranged as a 3 × 7 factorial. Treatments consisted of three Ca levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…In addition, supplementation of diets with phytase results in increased plasma inorganic P (Adeola 1995;Gentile et al 2003;Beaulieu et al 2007). In this study, we confirmed that pigs fed diets with higher dietary P and Ca also had higher serum P and Ca concentrations.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, supplementation of diets with phytase results in increased plasma inorganic P (Adeola 1995;Gentile et al 2003;Beaulieu et al 2007). In this study, we confirmed that pigs fed diets with higher dietary P and Ca also had higher serum P and Ca concentrations.…”
Section: Discussionsupporting
confidence: 77%
“…Typically, when swine diets are not in excess of the dietary P requirement, very little P is excreted in the urine because of reabsorption of P in the kidneys. It was reported previously that in swine, urine P was less than 0.5% of TP excreted (Baxter et al, 2003;Beaulieu et al, 2007); thus, the contribution from urine would be very small. Typically, manure (mixture of feces and urine) is stored for a period of time before land application.…”
Section: Discussionmentioning
confidence: 99%
“…Also, increasing dietary Ca from 4.7 to 11.6 g kg − 1 increased the amount of phytate-P (43.0%) excreted but decreased the output of water soluble P (57.0%). In pigs, Beaulieu et al (2007) found that E. coli phytase reduced total P and soluble P outputs, but high Ca:P ratios diminished this effect.…”
Section: Calcium Phytate Phytase and Excreta Qualitymentioning
confidence: 96%